Control of Pain and Dyspnea in Patients with Oncologic Disease in Acute Care: Non-Pharmacological Intervention - Ramos, A.; Tavares, AP; Lopes, M. J.; Mendes, F; Parreira, P.; Fonseca, C (My University, 2017)
Objective: To identify non-pharmacological strategies in the control of pain and dyspnea, in patient with oncological disease, in acute care. Methodology: Question in PI[C]O format was used and search at EBSCO (MEDLINE with Full TEXT; CINAHL, Plus with Full Text; British Nursing Index) retrospectively from 2009 to 2015. We included also guidelines by reference entities: Oncology Nursing Society (2011) National Comprehensive Cancer Network and Cancer Care Ontario, resulting in a total of 15 articles. Results: The gold standard for an adequate symptom control is a systematized assessment. Non-pharmacological measures: psycho-emotional support, hypnosis, counseling/training/ instruction, therapeutic adherence, music therapy, massage, relaxation techniques, telephone support, functional and respiratory reeducation increase health gains. Conclusion: The control of oncologic pain and dyspnea require a comprehensive and multimodal approach.